DIFUSI INOVASI PETANI DALAM PENGENDALIAN HAMA TERPADU (PHT) PADI SAWAH (Oryza sativa L.) MELALUI PEMANFAATAN TANAMAN REFUGIA DI KECAMATAN PANGANDARAN KABUPATEN PANGANDARAN - Yuddy Meiyudha Supharman; Maspur Makhmudi; Kusmiyati Kusmiyati (Jurnal Inovasi Penelitian, 2020)
Management of plant pest organisms results in considerable damage by quantity and lowered quality of the plant. The location survey carried out an interview with a supervisor explaining that the shed on unified pest control rice in the fields used refugia plants was previously carried out by farmers in some villages, one of the purbahayu villages, refugia plant planting less than the next growing season. The study is conducted in the Pangandaran District. Counting from march-july 2020. Assessments were obtained based on the farmers' criteria for raising rice in rice field and already applied pest control with refugia plants mixed in grouping with the village targeted by the Purbahayu village. The research approach uses age, education, a broader range of resources, information sources, communication channels, communicators, and innovators. With the result that the diffusion of innovation is affected by a powerful pellet by the role of distillers as innovators, resource information, and refining roles as communicators.